Recurrent ovarian dysgerminoma after laparoscopy. (1st January 2006) - Prado, S.; Yazigi, R.; Garrido, J.; Gonzalez, M.; Torres, R.; Oddo, D.
Abstract : To our knowledge, recurrent dysgerminoma at the site of tumor removal by laparoscopy in a patient with stage IA disease has not been previously reported. A woman with ovarian dysgerminoma treated by laparoscopy and tumor removed through the cul-de-sac recurred the 17 months later at the site of tumor removal. She was successfully treated with etoposide, bleomycin, and cisplatin chemotherapy with complete response. This case illustrates the potential for surgical site implant of an ovarian dysgerminoma; surgeons should follow strict guidelines when performing laparoscopic procedures for ovarian malignancies in order to prevent this type of incident.